2022
DOI: 10.1039/d2ra01167k
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation of proteins: electrostatic effects vs. hydration

Abstract: A phenomenological approach to the unfolding transition of proteins is given. The model treats quantitatively the effect of electrostatics as well as of hydration (Hofmeister effects).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(197 reference statements)
0
3
0
Order By: Relevance
“…This choice is well-borne out of various experimental studies on complex formation , and of protein denaturation in solution (cf. the discussion of this point in ref ). Then for a given T 0 = 265 K, a secure fit of all data displayed in Figure a can be easily reached.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This choice is well-borne out of various experimental studies on complex formation , and of protein denaturation in solution (cf. the discussion of this point in ref ). Then for a given T 0 = 265 K, a secure fit of all data displayed in Figure a can be easily reached.…”
Section: Resultsmentioning
confidence: 97%
“…Hence, the temperature T 0 is directly related to hydrations effects. We recently showed that this concept is also applicable to the unfolding of proteins …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation